Formulation, And Characterization Of Solid Lipid Nanoparticles (Sln) Of Isavuconazole - Kumar, Anup; Singh, Pushp Raj (Journal of Neonatal Surgery, 2025)
Since their introduction in the early 1990s, solid lipid nanoparticles (SLNs) have gained a reputation as the most potent lipid-based colloidal transporters. Isavuconazonium sulfate is the prodrug of the azole antifungal isavuconazole. The present study was based on the formulation, and characterization of solid lipid nanoparticles (SLNs) of isavuconazole. Isavuconazole was purchased from the (Sigma Aldrich, India). Stearic acid, Span 20, Tween 80, and ethanol were purchased from the SD Fine Chemicals, Mumbai. After, preformulation studies, SLNs were prepared using spray drying method. In results, Isavuconazole sample was observed as white, solid powder, with its characteristic odor. Stearic acid was observed as white solid flakes and odorless. Entrapment efficiency was observed in the range of 77.15±0.42 % to 84.34±0.21 %. It exhibits the remarkable and almost identical drug content in different SLNs. These have the efficient drug content’s release which represents the better solubility and optimized drug-excipient compatibility. The pH of solid lipid nanoparticles loaded with Isavuconazole was measured and found to be slightly acidic or alkaline. SLNs loaded with Isavuconazole showed almost identical response 120℃ when observed with the temperature in range of 50ºC to 300ºC. SLNs loaded with Isavuconazole showed the particle size in the range of 100-300 nm, in SEM analysis. The maximum drug release was seen in 10 hours i.e., 96.45±0.6, 94.31±0.4, 93.19±0.1, 91.10±0.4, 95.14±0.3 and 93.37±0.6 in F1, F2, F3, F4, F5 and F6, respectively. In concluded that SLNs loaded with Isavuconazole showed the significant in all the characterization parameters i.e., droplet size, drug content and in-vitro drug release. Isavuconazole is promising anti-fungal moiety with a wide range of potential health benefits. SLNs loaded with Isavuconazole can be utilized as anti-fungal or anti-microbial agent with sustained action...